Translating neuronal activity at the synapse: presynaptic calcium sensors in short-term plasticity - de Jong, Arthur P. H.; Fioravante, Diasynou (Frontiers in Cellular Neuroscience, 2014)
The complex manner in which patterns of presynaptic neural activity are translated into short-term plasticity (STP) suggests the existence of multiple presynaptic calcium (Ca2+) sensors, which regulate the amplitude and time-course of STP and are the focus of this review. We describe two canonical Ca2+-binding protein domains (C2 domains and EF-hands) and define criteria that need to be met for a protein to qualify as a Ca2+ sensor mediating STP. With these criteria in mind, we discuss various forms of STP and identify established and putative Ca2+ sensors. We find that despite the multitude of proposed sensors, only three are well established in STP: Munc13, protein kinase C and synaptotagmin-7. For putative sensors, we pinpoint open questions and potential pitfalls. Finally, we discuss how the molecular properties and modes of action of Ca2+ sensors can explain their differential involvement in STP and shape net synaptic output.